Diaphragmatic eventration plication repair with minimal access techniques: a case series - Oak, Aditya C.; Kalikar, Vishakha R.; Patel, Ankur K.; Patankar, Roy V. (International Surgery Journal, 2021)
Diaphragmatic eventration is a rare pathological condition occurring in <0.05% individuals causing the diaphragm to permanently ascend into the chest due to partial or complete replacement of diaphragmatic musculature by fibroblastic tissue. Congenital diaphragmatic eventration rarely presents among adults with most patients remaining asymptomatic only to be diagnosed incidentally after chest radiography. Symptomatic patients can present with dyspnoea, orthopnoea, recurrent lower respiratory tract infections or gastrointestinal symptoms. Management varies according to symptoms with asymptomatic cases requiring no intervention and plication being the standard, well-described technique for symptomatic cases. Here we described two cases with eventration approached using different minimal access techniques.